Development of a Concept Mastery Test Instrument Based on the C-R-E-A-T-E Model on the Saponification Topic: Validity and Reliability Analysis - Evita Puteri Amelia; Wawan Wahyu; Galuh Yuliani (FKIP - Universitas Riau, 2026)
This study aimed to develop a concept mastery test instrument based on the C-R-E-A-T-E (Connecting – Restructuring – Elaborating – Applying – Tasking – Evaluating) learning model on the saponification topic and to examine its validity and reliability. Assessment of concept mastery is essential in chemistry education due to the abstract and hierarchical nature of chemical concepts, particularly in topics such as saponification that involve conceptual integration and application. This research employed a Research and Development (R&D) approach by adapting the 4-D model, limited to the Define, Design, and Develop stages. The instrument consisted of 20 multiple-choice items constructed according to the stages of the C-R-E-A-T-E model. Data were collected through a limited field trial and analyzed using item validity, reliability, difficulty index, and discrimination index analyses. Item validity was examined using the point biserial correlation, while reliability was measured using the Kuder–Richardson Formula 20 (KR-20). The results showed that most items were valid, with the test demonstrating high reliability. Analysis of item difficulty indicated that the majority of items were categorized as easy to moderate, while discrimination analysis revealed that most items were able to distinguish effectively between students with high and low levels of concept mastery. These findings indicate that the developed instrument is valid, reliable, and suitable for measuring students’ concept mastery of saponification within the C-R-E-A-T-E learning framework.